Análisis del proceso de control vectorial en el Distrito de Salud Palenque Vinces 12D05 - Plúas Carriel, Byron Andrés (2021)
This case study will focus on analyzing how the internal processes are carried out for this activity, therefore, it will try to know what factors affect the normal development of the activities of the vector control department in the Palenque health district - Vinces 12D05, for which a qualitative methodology will be applied that allows the collection of information necessary for the development of the research, a descriptive study will be used, accompanied by scientific, inductive and documentary methods that complement the obtaining of information. The sub-line of research in which the case study is related is "Public and private companies and institutions" of the trade career, this research will be complemented with the use of the survey technique that applies a series of standardized procedures, and that from its application the data of the sample estimated as representative of a population will be collected, processed and analyzed in this case the workers of the vector control department of the Palenque health district - Vinces 12D05, for this purpose a questionnaire will be created to be applied and obtain the necessary information.